Diagnostic Value of Unenhanced Computerized Tomography Urography in the Evaluation of Acute Renal Colic - Jia-Hwia Wang; Chao-Jung Wei; Cheng-Yen Chang (Kaohsiung Journal of Medical Sciences, 2003)
This study prospectively evaluated the diagnostic value of unenhanced computerized tomography (CT) urography in patients with acute renal colic. Fifty-nine patients with clinical manifestations of acute renal colic underwent unenhanced helical CT to evaluate urinary tract abnormalities. Reformatted three-dimensional CT urography was performed in all patients. The findings were correlated with ureteroscopy, surgical findings, histopathologic findings, and clinical course. CT urography detected urinary abnormalities in 57 of 59 patients with the clinical manifestation of acute renal colic, including 45 cases of urolithiasis, three urinary malignancies, one congenital abnormality, and eight ureteral strictures (due to chronic inflammation or fibrosis). CT urography showed negative findings in the urinary system in two patients, and after clinical follow-up, urinary abnormality was excluded in these patients. Incidental findings of extrarenal disease were noted in six patients (pulmonary abnormalities, n = 2; gallstones, n = 4). Only one patient with urolithiasis was misdiagnosed as having a renal tumor by CT urography. The sensitivity and specificity of CT urography in diagnosing urolithiasis was 97.8% (44/45) and 100% (14/14), respectively. Three-dimensional CT urography is a newly developed modality to evaluate anomalies of the urinary tract. The highly accurate diagnostic value of CT urography makes it a suitable alternative or substitutive modality in patients with acute flank pain.